The Killekyatha, nomadic folk artists of northern Mysore - Morab, S. G., 1932- (Memoir (Anthropological Survey of India), 1977)
On a group of scheduled caste people; field work conducted in the village of Kalikapur, Bijapur District, Karnataka, during 1970-1971.